Comparison of Thermally Grown Carbon Nanofiber‐Based and Reduced Graphene Oxide‐Based CMOS‐Compatible Microsupercapacitors. Issue 2 (20th November 2020) - Vyas, Agin; Hajibagher, Simin Zare; Li, Qi; Haque, Mazharul; Smith, Anderson; Lundgren, Per; Enoksson, Peter
Abstract : Microsupercapacitors as miniature energy storage devices require complementary metal–oxide–semiconductor (CMOS) compatible techniques for electrode deposition to be integrated in wireless sensor network sensor systems. Among several processing techniques, chemical vapor deposition (CVD) and spin coating, present in CMOS manufacturing facilities, are the two most viable processes for electrode growth and deposition, respectively. To make an argument for choosing either of these techniques to fabricate MSCs utilizable for an on‐chip power supply, we need a comparative assessment of their electrochemical performance. Herein, the evaluation of MSCs with CVD‐grown carbon nanofiber (CNF)‐based and spin‐coated reduced graphene oxide (rGO)‐based electrodes is reported. The devices are compared for their capacitance, energy and power density, charge retention, characteristic frequencies, and ease of fabrication over a large sweep of scan rates, current densities, and frequencies. The rGO‐based MSCs demonstrate 112 μF cm −2 at 100 mV s −1 and a power density of 12.8 mW cm −2 . The CNF‐based MSCs show 269.7 μF cm −2 and 30.8 mW cm −2 . CVD‐grown CNF outperforms spin‐coated rGO in capacitive storage at low frequencies, whereas the latter is better in terms of charge retention and high‐frequency capacitance response. Abstract : Herein, a direct comparison of spin‐coated and plasma‐grown microsupercapacitors (MSCs) for integration in complementary metal–oxide–semiconductor (CMOS) technology for powering wireless sensor nodes is presented. The plasma‐grown carbon nanofiber‐based MSC reveals a better performance in terms of capacitance and power density, whereas the spin‐coated reduced graphene oxide MSCs can be fabricated with a high wafer yield.